A Computational Bibliometric Analysis of Game Advertising using VOSviewer - Ginting, Yogie Rinaldy (Universitas Komputer Indonesia, 2023)
The purpose of this study is to perform a computational bibliometric analysis of the Term “Game advertising” by combining mapping analysis using VOSviewer Publish or Perish software, and Google Schoolar. The method used is a bibliometric and descriptive quantitative approach. The data obtained is a search result based on the keyword